Cultivation of Caisim Mustard (Brassica juncea L.) in The NFT (Nutrient Film Technique) Hydroponic System - Agustina, Hilda; Muhammad Priyatama Haibir; Fidel Harmanda Prima (Program Studi Teknik Pertanian Universitas Hasanuddin, 2024)
Plant cultivation using the NFT (Nutrient Film Technique) hydroponic system is quite widely used by people in urban areas in plant houses. Suboptimal provision of nutrients causes unsatisfactory plant production. Less than optimal provision of nutrients for plants will affect plant production. Cultivation of caisim mustard plants in hydroponic systems will also be beneficial in urban areas where land is very limited. The design of the NFT hydroponic system also affects the provision of nutrients for Caisim mustard plants. This study aims to determine the performance of the NFT hydroponic system (gutter discharge) and the concentration of AB Mix in the cultivation of caisim (Brassica Juncea L.). The method used in this study was a Randomized Group Factorial Design (RAKF) with two treatment factors, namely water flow discharge (Q) and concentration of nutrient solution (N) consisting of three treatments and three replications. The research parameters were plant height, number of leaves, plant fresh weight, plant dry weight and plant productivity. It was concluded that the water flow discharge and concentration of nutrient solution had a significant effect on plant growth, number of leaves and fresh weight of plants.